The Identification Of Ticks That Have The Potential To Transmit Diseases To Human (Ticks Borne Diseases) That Infested Sumatran Tiger (Panthera tigris sumatrae) Based On Morphological Analysis In West Sumatra Province - Hidayati, Lisa; Zulfanedi, Yoli; Viawan, Bilan Diurai; Rahmadanti, Tika; Alhamda, Syukra; Gusmiati, Rita (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
The Sumatran tiger (Panthera tigris sumatrae) is endemic to the island of Sumatera. Ticks-borne diseases are diseases caused by bacteria, viruses and other parasites carried by intermediary animals, namely insects (Arthropods) especially ticks. We aimed to focus on identifying the ticks parasitizing Sumatran tigers (Panthera tigris sumatrae) from Pasaman based on morphological analysis. The taxonomic identification of ticks collected from Panthera tigris sumatrae was performed based on the morphology of adults with loupe and microscope at a magnification of 10 x 40. We revealed three species of ticks including, Amblyomma javanense, Haemaphysalis bispinosa, Haemaphysalis wellingtoni. All three species are known to feed on humans and appear to have established populations within Indonesia. Three spesies of ticks in Sumatran tigers (Panthera tigris sumatrae) from Pasaman were found. The recent detection of ticks in Indonesia highlights the need for more extensive research into these parasites and potential disease vectors, both within the island nation and across Asia more broadly